Quantification of galantamine in Narcissus tazetta and Galanthus nivalis (Amaryllidaceae) populations growing wild in Iran. Issue 2 (14th March 2017) - Rahimi Khonakdari, Majid; Mirjalili, Mohammad Hossein; Gholipour, Abbas; Rezadoost, Hassan; Moridi Farimani, Mahdi
Abstract: Galantamine (GAL), a morphine-like alkaloid produced by some members of the Amaryllidaceae plant family, is a possible therapeutic agent in Alzheimer's disease because of its central cholinergic effects. GAL has been extracted from the plant sources or produced synthetically for pharmaceutical use. Limited supply of the natural source and high cost of synthetic production has led to a search for alternative sources of this valuable compound. In the present study, a total of six Galanthus nivalis populations (GNPs) and 11 Narcissus tazetta populations (NTPs) were collected across different regions of Iran and were then subjected to the high-performance liquid chromatography analysis for their GAL quantification. The GAL content ranged from 0.05 to 0.36 mg/g dry weight (DW) in the bulbs of GNPs, and from 0.03 to 0.33 mg/g DW in the bulbs of NTPs. Maximum content of GAL (0.36 and 0.33 mg/g DW) was measured in the Zirab population of G. nivalis and Ghaemshahr population of N. tazetta, respectively. Our results provided a suitable material for further agronomical and biotechnological strategies for enhanced production of valuable GAL compound on a large scale.